Foster Cultural Synergy and Innovation, Communicate to Revive Coastal Economy Sustainably Post-Pandemic - Subekti, Priyo; Komariah, Kokom; Perbawasari, Susie (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2025)
The objective of this study is to examine strategies of adaptation and innovation among MSME actors at Pangandaran Beach, with an emphasis on utilizing local cultural values to aid economic and tourism recovery post-COVID-19. The research identifies the key challenges faced by MSMEs in adapting to new norms, including issues with capital, technological adaptation, human resources development, and policy changes. Employing a qualitative case study methodology, the study gathers in-depth insights from 12 MSME actors through interviews to understand the challenges and opportunities faced during the pandemic. The major findings indicate that MSMEs at Pangandaran Beach have encountered significant challenges but also possess opportunities for growth and resilience. Innovations, collaborative ventures, governmental support, and business networking are identified as crucial factors that can bolster MSME competitiveness and enable them to overcome post-pandemic setbacks. In conclusion, the study suggests that a holistic strategy involving all stakeholders is essential for MSMEs to not only recuperate from the impacts of the pandemic but also to emerge as integral components of a sustainable tourism ecosystem, contributing to the broader economic recovery.